Operation Biting : the 1942 parachute assault to capture Hitler's radar - Hastings, Max (HarperCollins, 2024)
"Operation Biting was one of the most thrilling British special forces raids of World War II, and probably the most successful. In February 1942 RAF intelligence was baffled by a newly identified radar network on the coast of Nazi-occupied Europe, codenamed Würzburg. The brilliant scientist Dr R.V. Jones proposed an assault to capture key components. The nearest accessible enemy set stood upon a steep cliff at Bruneval in Normandy. Amid heavy snow 120 men landed, some of whom were misdropped almost two miles from their objective. They nonetheless launched the assault, dismantled the German radar, and after three nail-biting hours in France and a fierce battle with Wehrmacht defenders, escaped in the nick of time by landing-craft across stormy seas to Portsmouth. Taking us from the War Room to boots-on-the-ground action, and recounted in Hastings's signature bestselling style, Operation Biting tells a story that has become almost forgotten yet deserves to rank among the epic tales of courage and daring that took place in the greatest conflict in history"--Publisher's description.